Towards ecological, socioeconomic and cultural sustainability of marine ecosystem services. Issue 1 (27th December 2020) - Nishijima, Shota; Belgrano, Andrea
Abstract : The ocean provides us a variety of ecosystem services such as the supply of fish and shellfish, the provision of opportunities to enjoy recreational diving in coral reefs, and the regulation of wave disaster impacts by coastal mangrove forests. This special feature presents the current status in various aspects of marine ecosystem services and gives an opportunity to consider their maintenance and sustainability for our future lives.